2019
DOI: 10.21733/ibad.613920
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Dönem Çocuklarının Öz Düzenleme Becerileri ile Benlik Algıları Arasındaki İlişkisinin İncelenmesi

Abstract: This article was checked by Turnitin. Similarity Index 11%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Accordingly, it was found that girls had higher self-regulation and social-emotional adaptation than boys, but there was no gender difference in emotion regulation. Researches have shown that there are gender differences in self-regulation in early school years (Ponitz et al, 2008;Matthews et al, 2009;Sezgin et al, 2019;Alwaely et al, 2021;Tuzcuoğlu et al, 2019). In addition, in some studies are found that women typically exhibit higher levels of selfregulation than men throughout life (Kochanska et al, 1997;Kochanska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it was found that girls had higher self-regulation and social-emotional adaptation than boys, but there was no gender difference in emotion regulation. Researches have shown that there are gender differences in self-regulation in early school years (Ponitz et al, 2008;Matthews et al, 2009;Sezgin et al, 2019;Alwaely et al, 2021;Tuzcuoğlu et al, 2019). In addition, in some studies are found that women typically exhibit higher levels of selfregulation than men throughout life (Kochanska et al, 1997;Kochanska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, children with fathers who finished high school exhibited significantly improved social skills scores in contrast to those whose fathers had primary or secondary school education. Limited research exists that scrutinizes children's behaviour, emotion regulation, and social capabilities in relation to the sibling count, parents' employment status, and educational achievements (Çomak, 2022;Tuzcuoğlu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle araştırmanın modeli ilişkisel tarama modelidir. (Astarlar, 2019;Daggul & Gürşımsek, 2019;Tuzcuoğlu, Efe Azkeskin, İlçi Küsmüş & Cengiz, 2019;Tozduman Yaralı & Güngör Aytar, 2017;Raffaelli, Crockett & Shen, 2005), cinsiyet ile özdüzenleme becerileri arasında ilişki olmadığını gösteren çalışmalar da bulunmaktadır. Almeqdad, Al-Hamouri, Zghoul, Al-Rousan ve Whitebread (2016) tarafından yapılan araştırmada, Ürdünlü okul öncesi çocukların özdüzenleyerek öğrenme becerisi cinsiyet ve ebeveynlerin eğitim durumu değişkenleri açısından incelenmiştir.…”
Section: Yöntem Araştırmanın Modeliunclassified
“…The preschool duration is a critical period in the child's development, and some factors, such as the child's innate characteristics and environmental factors, affect the development during this period (Tuzcuoğlu et al, 2019). The environmental factors are closely related to development.…”
Section: Introductionmentioning
confidence: 99%